PENGETAHUAN EKOLOGIS TRADISIONAL DAN PELESTARIAN ETNOLINGUISTIK BERKELANJUTAN DI KAWASAN CAGAR BIOSFER RINJANI LOMBOK, INDONESIA - Rabiyatul Adawiyah (Universitas Sultan Ageng Tirtayasa, 2026)
The Rinjani Biosphere Reserve in Lombok Island, Indonesia, represents a unique ecological and geographical landscape while also serving as a living space for diverse ethnolinguistic communities whose Traditional Ecological Knowledge (TEK) is deeply embedded in local languages. However, the expanding dominance of Indonesian in the Bayan Indigenous Area has accelerated language shift, leading to the erosion of ecological lexicon and weakening oral traditions essential for biodiversity governance. This study aims to examine the integration of local TEK with sustainable ethnolinguistic preservation in the Rinjani Biosphere Reserve. Employing a qualitative ethnolinguistic approach, data were collected through semi-structured interviews with thirty informants, participant observation, and systematic documentation of local language use. Thematic and ethnosemantic analyses were conducted to link ecological domains with lexical structures, toponyms, and customary regulations (awig-awig). The findings reveal a functional interdependence between ecological lexicon, customary norms, and conservation practices. This study contributes a biocultural framework that positions indigenous linguistic knowledge as a vital component of sustainable ecosystem management and cultural heritage preservation.